ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF BIXIN PIGMENT FROM ANNATTO (Bixa orellana L.) SEEDS - Pipin T. Kurniawati; H. Soetjipto; Leenawati Limantara (Universitas Gadjah Mada, 2007)
Research on Bixa orellana L. have been done to isolate, identify and determine bixin percentage, the antioxidant and antibacterial activities of bixin from B. orellana seed. Isolation and identification of bixin was done by thin layer chromatography (TLC), column chromatography, chemical test of bixin and UV-Vis double beam spectroscopy. Percentage of bixin was calculated by JECFA method, the antioxidant activity was determined by DPPH (1-1 diphynilpicrylhidrazil) method while antibacterial activity was analyzed by the use of agar diffusion method. Thin layer chromatography (TLC) for the crude extract contained 5 spot, where spot 5th was bixin. Bixa orellana has 75±3% of bixin. Antioxidant activity of bixin had IC50 548.5±20.0 ppm. Whereas the antibacterial activity of bixin against the Escherichia coli and Staphylococus aureus could be classified as weak inhibition category at 500-750 μg and medium inhibition category at 1500 μg.